The retreat eaudiobook - Pearse, Sarah (Detective Elin Warner, 2022)
AN INSTANT NEW YORK TIMES BESTSELLER! From the New York Times bestselling author of The Sanatorium , a Reese’s Book Club pick, here, Detective Elin Warner uncovers the truth behind the suspicious deaths on a stunning island getaway. “Devilish and deliciously twisty.” — People “The suspense inexorably builds to a stunning climax.” —David Baldacci, #1 New York Times bestselling author of Long Shadows They couldn’t wait to stay here. An idyllic wellness retreat has opened on an island off the English coast, promising rest and relaxation—but the island itself, known locally as Reaper’s Rock, has a dark past. Once the playground of a serial killer, it’s rumored to be cursed. But now they can’t leave. A young woman is found dead below the yoga pavilion in what seems to be a tragic fall. But Detective Elin Warner soon learns the victim wasn’t a guest—she wasn’t meant to be on the island at all. And they would do anything to escape. The longer Elin stays, the more secrets she uncovers. And when someone else drowns in a diving incident, Elin begins to suspect that there’s nothing accidental about these deaths. But why would someone target the guests at this luxury resort? Elin must find the killer—before the island’s history starts to repeat itself. Most came to recharge and refresh. But someone’s here for revenge.